2008
DOI: 10.1002/mrm.21590
|View full text |Cite
|
Sign up to set email alerts
|

Local excitation black blood imaging at 3T: Application to the carotid artery wall

Abstract: A novel approach for imaging large sections of the carotid artery wall at isotropic spatial resolution is presented. Local excitation by means of 2D excitation pulses was combined with a diffusion-prepared segmented steady-state black-blood gradient echo technique enabling the assessment of the carotid arterial wall over a range of up to 15 cm. The carotid arteries of five healthy volunteers were imaged with the proposed technique. Signal-to-noise ratio (SNR), wall-lumen contrast-tonoise ratio (CNR), and vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…MSDE has been combined with 3D acquisition techniques for effective blood suppression in a large volume (37-38) because of its low dependency on flow direction. It can also be utilized post-contrast due to its T 1 insensitivity.…”
Section: Plaque Burden Measurementsmentioning
confidence: 99%
“…MSDE has been combined with 3D acquisition techniques for effective blood suppression in a large volume (37-38) because of its low dependency on flow direction. It can also be utilized post-contrast due to its T 1 insensitivity.…”
Section: Plaque Burden Measurementsmentioning
confidence: 99%
“…In addition, parts of the heart distant from the surface coils, such as the inferior and lateral walls, can induce myocardial signal loss and lead to false-negative diagnosis [11]. Some authors have reported that weak diffusion-sensitizing gradients can efficiently nullify the blood pool signal by dephasing all moving spins prior to the imaging sequence [13][14][15]. Recently, Nguyen et al reported that diffusion-weighted (DW) black blood imaging of the heart is feasible in healthy subjects, with reference to IR FSE T2-weighted sequences [16].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the carotid arteries can be imaged using phased‐array coils and well‐tested multicontrast imaging protocols such as bright‐ and black‐blood techniques 82. All of these make the carotid artery the most commonly assessed vessel in MRI studies of atherosclerosis 23, 83, 84, 85…”
Section: Multimodality Imaging Techniquesmentioning
confidence: 99%